Instructional Set Moderates the Effect of GRE on Faculty Appraisals of Applicant Competence: A Vignette Study With Implications for Holistic Review - Hernández-Colón, Isabelle Rios; Caño, Annmarie; Wurm, Lee H.; Sanders, Gavin; Nava, Jennifer (Frontiers in Psychology, 2021)
While there is movement to create more equitable and holistic admission review processes, faculty continue to place strong emphasis on a single piece of information when making admissions decisions: standardized test scores. This study used an experimental design to test whether instructions provided to faculty prior to assessing doctoral applicants could support holistic review by reducing the weight of the general record examination (GRE) in faculty appraisals of competence and merit for graduate study. Tenured and/or tenure-track faculty (N=271) were randomly assigned to one of three instructional conditions: Control (no instruction), “Diamond in the Rough,” and “Weed Out.” In addition, faculty participants were randomly assigned to read one of two vignettes of a prospective first-generation student who either received high or average GRE scores. Faculty then rated the applicant’s competence using a three-item survey. As expected, faculty who read the vignette describing the candidate with the high GRE rated him as more competent than faculty who read the average GRE vignette. In addition, being instructed to seek out diamonds in the rough buffered the effect of the GRE score on competence. Faculty were also asked to indicate whether they would need additional information to make an admissions decision. They were more likely to ask about grades and research skills than about psychosocial factors that might contextualize the candidate’s performance and perceived competence. The results of this study have implications for creating more equitable doctoral admissions processes that center equity, diversity, and inclusion in decision making.